Predictive Design Customization Using Machine Learning - Nath, Sumendra Nath Singh; Kumari, Vandna Kumari (Journal of Recent Innovations in Computer Science and Technology, 2026)
The contemporary product success is heralded through customization and personalization. The present paper proposes a machine learning-based system that enhances adaptive, personalised product configuration based on the analysis of user customization preferences, feedback, and behaviour data. The framework can learn the customer needs using clustering algorithms, predictive analytics, feature selection models, and dynamically generate the design configuration recommendations. Some application areas of the system can include consumer electronics, apparel, and automotive interiors to produce customized product variants. Such a pipeline based on data is suggested, which would involve no-supervised learning in segmentation and supervised learning in predicting product features. The innovation enables companies to make customized, modular products with an increased appeal in the market.